Penurunan Cacat Produk Kursi Plastik PT PQR dengan Metode Quality Qontrol Circle (QCC) - 10070217036, M Akbar Halomoan Lubis; Iyan Bachtiar (UNISBA Press, 2024)
Abstract. PT PQR is a company engaged in manufacturing in Indonesia, the products produced are plastic chairs. Plastic chairs are the product with the highest demand at PT PQR. PT PQR has nonconformities. In terms of production completion, the company has set a maximum defect rate of 1% for defects in the method caused by human error factors which result in the product not being in accordance with the company's requirements. The aim of this research is to analyze how to reduce product defects in plastic chair products at PT PQR. The research uses the Quality Control Circle (QCC) method. At the plan stage, planning is to look for the most dominant types of defects and look for the root causes of defective products. There are five types of defects for plastic chair products. By making a Pareto diagram and looking for the causes of defects in plastic chair products. Based on the Pareto diagram, the research focuses on improving 1 type of defect, namely the bubbles defect type, the factors causing this defect use the fishbone diagram. Do stage: Once the cause of the defect is known, determine targets and objectives in corrective action and identify defective products and is assisted by the 5W+1H tools. In the check stage, further inspection was carried out using 7 tools, the highest value was obtained, namely 1,411. The next stage was the action stage, at this stage quality control was carried out in the form of providing proposals for training employees, selecting materials, checking machines regularly, and providing standard work operations. Abstrak. PT PQR adalah salah satu perusahaan yang bergerak pada bidang manufaktur di Indonesia, produk yang dihasilkan adalah produk kursi plastik. Kursi plastik merupakan produk dengan permintaan yang paling tinggi di PT PQR. PT PQR memiliki ketidaksesuaian dalam hal penyelesaian produksi, perusahaan telah menetapkan tingkat kecacatan maksimal 1% untuk terjadinya cacat pada metode yang disebabkan oleh faktor human error yang mengakibatkan produk tidak sesuai dengan kebutuhan perusahaan. Tujuan penelitian ini adalah untuk menganalisis bagaimana cara mengurangi produk cacat pada produk kursi plastik di PT PQR. Penelitian menggunakan metode Quality Qontrol Circle (QCC). Pada tahap plan (perencanaan) untuk mencari jenis cacat yang paling dominan dan mencari akar penyebab terjadinya produk cacat. Jenis cacat untuk produk kursi plastik diperoleh sebanyak lima jenis. Dengan membuat diagram Pareto dan mencari penyebab terjadinya cacat pada produk kursi plastik. Berdasarkan diagram Pareto, penelitian fokus memperbaiki 1 jenis cacat yaitu jenis cacat bubbles, faktor-faktor penyebab cacat tersebut menggunakan fishbone diagram. Tahap do setelah diketahui penyebab terjadinya cacat, menentukan sasaran dan tujuan dalam tindakan perbaikan dan identifikasi produk cacat dan dibantu oleh tools 5W+1H. Tahap check dilakukan pemeriksaan lebih lanjut dengan menggunakan 7 tools, didapatlah nilai yang paling tinggi yaitu sebesar 1.411. Tahap selanjutnya adalah ialah tahap action, pada tahap ini dilakukan pengendalian kualitas dalam bentuk pemberian usulan untuk melakukan pelatihan kepada karyawan, pemilihan material, pengecekan mesin secara berkala, dan pemberian standar operasi kerja.